(untitled) (Ocean and Coastal Research, 2022)
The objective of this study is to compare the physical characteristics of circulation, salinity structure and transport in theItajaí-Açu and Itajaí-Mirim estuaries. Due to its importance, the Itajaí-Açu estuary has been studied in the last decade.However, its main tributary, the Itajaí-Mirim has never been assessed, especially as an opportunity to comparativelyinvestigate the flow behavior of salt wedge estuaries with different widths and depths. Field data were acquired during twocampaigns that covered the complete semi-diurnal tidal regimes during spring and neap tides. Water level, total transportvolume, current and salinity were recorded hourly and synoptically at cross-sections in each estuary. The campaigns wereconducted during a prolonged period of low river discharge. The tidal range during the spring and neap tide campaignswere of approximately 1.2 and 0.4 m, respectively. At the Itajaí-Açu and Itajaí-Mirim cross-sections, the peak ebb and floodcurrents were -0.8 and -0.6 m s-1 and 0.8 and 0.4 m s-1, respectively, during the spring tide campaign, and classified aswell mixed and highly stratified estuaries, respectively. During the neap tide campaign, both estuaries were classified assalt wedge. The dominant mechanism was the salt transport by advection due to fluvial advection in both estuaries andcampaigns. The landwards salt transport, which resulted from dispersive processes, was only important during neap tidefor the Itajaí-Açu estuary.